Multiannual forecasts of Atlantic U.S. tropical cyclone wind damage potential. Issue 7 (14th April 2015) - Caron, Louis‐Philippe; Hermanson, Leon; Doblas‐Reyes, Francisco J.
Abstract There are strong decadal variations in Atlantic hurricane activity, with an active period in the 1950s and 1960s, a quiescent period from the 1970s through the early 1990s and a resurgence in activity since the mid‐1990s. Using an index that relies on subpolar gyre temperature and subtropical sea level pressure, two quantities with links to hurricane activity, we show that it is possible to construct reliable 5 year mean forecasts of both basin‐wide tropical cyclone activity as well as wind energy associated with hurricanes making landfall along the U.S. coastline. Furthermore, the index is capable of reproducing the major decadal shifts in activity observed over the last 50 years. This is the first time that a forecast system shows significant skill of a landfalling hurricane characteristic at the multiannual time scale and, as such, shows great promise as a valuable climate service product.